Impact of Digital Technology Access and Structural Factors on Women’s Labor Force Participation in Indonesia - Riski Aprilianti Baharuddin; Retno Fitrianti; Rhena J (Efficient: Indonesian Journal of Development Economics, 2025)
This study examines the effects of digital technology access, gender equality, regional economic development, and minimum wage policy on women’s labor force participation in Indonesia. Using an annual provincial panel data set for the period 2015-2024 (t = 10), yielding 340 annual observations, the analysis applies a dynamic panel regression based on an Error Correction Model to distinguish long-run relationships from short-run dynamics. The results confirm a long-run relationship between digitalization, the gender development index, gross regional domestic product per capita, the provincial minimum wage, and women’s labor force participation. In the long run, the gender development index, gross regional domestic product per capita, and the provincial minimum wage have positive and statistically significant effects on women’s participation, while digitalization has a positive but not yet significant effect. In the short run, changes in digitalization, the gender development index, and gross regional domestic product per capita positively and significantly affect changes in women’s labor force participation, whereas changes in the provincial minimum wage are not significant. These findings suggest that digitalization mainly acts as a short-run opportunity trigger, while progress in gender equality, rising regional prosperity, and an adequate minimum wage function as key structural determinants of stronger women’s labor force participation in the digital economy.